National solid waste management reformation symposium 2025 - Ngien, Su Kong (The Institution of Engineers Malaysia, 2025)
On 6 May 2025, the National Solid Waste Management Department, under the Ministry of Housing & Local Government, organised the National Solid Waste Management Reformation Symposium 2025, in collaboration with the Waste Management Association of Malaysia and the Housing & Local Government Training Institute (I-KPKT).